Idicators of social security in the social policy of Ukraine: theoretical and methodological approaches of their estimation - Ільчук, Л. І. (SOCIOPROSTIR: the Interdisciplinary Online Collection of Scientific Works on Sociology and Social Work, 2016)
In this paper we investigated the classification of methods of calculating social security in Ukraine. It describes the state of the social security scheme of the zonal, namely safety zone danger zone > > Zone threats. Analyzed instructional techniques that are used in the calculation of social security. Described the experience of post-Soviet states on indicators of social security. It focused on the fact that the performance indicators of social policy is characterized by the results of social policies to achieve these goals, the state of society and social welfare of the citizens of Ukraine. They characterize the extent of the negative results of the (non-exercise), social policies in individual directions.